Low-Dose Prophylaxis versus On-Demand Therapy in Hemophilia Management: A Systematic Review and Meta-Analysis of Clinical Outcomes and Cost-Effectiveness in Resource-Limited Settings - Rijalun Arridho; Rudy Afriant (Open Access Indonesian Journal of Medical Reviews, 2026)
Hemophilia A and B impose a catastrophic burden in resource-limited settings (RLS), where the standard of care—high-dose primary prophylaxis—remains economically inaccessible. Consequently, patients rely on episodic (on-demand) therapy, which fails to prevent the debilitating cascade of hemophilic arthropathy. This study aims to validate Low-Dose Prophylaxis (LDP) as a superior standard of care by synthesizing real-world clinical data. We conducted a systematic review and meta-analysis of pivotal studies published between 2011 and 2025, encompassing cohorts from India, Indonesia, China, Pakistan, and Ivory Coast in accordance with PRISMA guidelines. Interventions included low-dose Factor VIII/IX (10–25 IU/kg), Extended Half-Life (EHL) factors, and Emicizumab. Primary outcomes were Annualized Bleeding Rate (ABR) and Hemophilia Joint Health Score (HJHS). The clinical meta-analysis included 127 pediatric and adolescent subjects. LDP demonstrated a statistically significant reduction in ABR compared to on-demand therapy (Pooled Mean Difference: -8.14; 95% CI: -10.5 to -5.7; p<0.001). EHL prophylaxis reduced mean ABR from 6.0 to 0.07. Joint health improved significantly, with HJHS scores decreasing from 5.42 to 2.28 (p=0.0013) post-intervention. Quality of life metrics, including school absenteeism, showed profound improvements. In conclusion, low-dose prophylaxis is a clinically superior and viable strategy in RLS, effectively arresting the progression of arthropathy and improving functional independence. Healthcare policy in developing nations must prioritize prophylactic models over episodic care to prevent irreversible musculoskeletal disability.